Implementation research on sustainable electrification of rural primary care facilities in Ghana and Uganda. (6th November 2020) - Javadi, Dena; Ssempebwa, John; Isunju, John Bosco; Yevoo, Lucy; Amu, Alberta; Nabiwemba, Elizabeth; Pfeiffer, Michaela; Agyepong, Irene; Severi, Luc
Abstract: Access to energy is essential for resilient health systems; however, strengthening energy infrastructure in rural health facilities remains a challenge. In 2015–19, 'Powering Healthcare' deployed solar energy solutions to off-grid rural health facilities in Ghana and Uganda to improve the availability of maternal and child health services. To explore the links between health facility electrification and service availability and use, the World Health Organization (WHO), in partnership with Dodowa Health Research Centre and Makerere University School of Public Health, carried out an implementation research study. The objectives of this study were to (1) capture changes in service availability and readiness, (2) describe changes in community satisfaction and use and (3) examine the implementation factors of sustainable electrification that affect these changes. Data were collected through interviews with over 100 key informants, focus group discussions with over 800 community members and health facility assessment checklist adapted from the WHO's Service Availability and Readiness Assessment tool. Implementation factors were organized using Normalization Process Theory constructs. The study found that access to energy is associated with increased availability of health services, access to communication technologies, appropriate storage of vaccines and medicines, enhanced health worker motivation and increased community satisfaction. Implementation factors associated with improved outcomes include stakeholder engagement activities to promote internalization, provision of materials and information to encourage participation, and establishment of relationships to support integration. Barriers to achieving outcomes are primarily health systems challenges—such as drug stockouts, lack of transportation and poor amenities—that continue to affect service availability, readiness and use, even where access to energy is available. However, through appropriate implementation and integration of sustainable electrification, strengthened energy infrastructure can be leveraged to catalyze investment in other components of functioning health systems. Improving access to energy in health facilities is, therefore, necessary but not sufficient for strengthening health systems.